NILAI NILAI PENDIDIKAN MORAL DALAM GURINDAM DUA BELAS KARYA RAJA ALI HAJI - Miftahuddin Miftahuddin; Nofmiyati Nofmiyati (An-Nida', 2015)
Religion came a lot of logical consequences on its functions for human life. First, religion guided to ideal ethic and moral. Second, the religion keep look of deviation of them. Third, the religion develop them both in all dimension of human life accordance with dynamics of culture. Human being is consists of body (jasad) and soul (ruh). The unity of them both distinguished form the other creatures. You know that there is passion in soul to do good or bad. For this there is a belief and godfearing to versus it. When man is able to versus the bad passion, it means that the man has got a good personality and moral.